The Use of Stem Cells for Beauty Therapy Islamic Law Perspective - Rizka Rizka; M. Junaidi; Nunik Nurhayati; Septarina Budiwati (Budapest International Research and Critics University, 2022)
This research was motivated by the discovery of Stem Cells which are widely used for medical treatment, but are known to be useful for beauty. Its ability to replace dead cells with new, young and healthy cells is needed for anyone who wants to keep beautiful and healthy, far from illness caused by decreased function or damage to organs. So many women use stem cells to delay aging. The purpose of this study is to find out the law on the use of Stem Cells in an Islamic perspective, because the source of Stem Cell retrieval is still in the pros and cons. study uses the library method by collecting data about stem cells and their uses for beauty and Islamic law from various sources including books and journals. The results showed that from the perspective of Islamic law the use of stem cells for aesthetic beauty and anti aging is prohibited for any reason because it is only for non-emergency needs. The use of stem cells is more used for benefits and does not violate norms, ethics and religion, does not cause damage and respects the Creator's creation.